Induction of EROD activity in European eel (Anguilla anguilla) experimentally exposed to B(a)P and βNP - BONACCI, S.; CORSI, I.; CHIEA, R.; REGOLI, S.; FOCARDI, S. (Environment International, 2003)
The induction of liver ethoxyresorufin O-deethylase (EROD) activity was investigated in the European eel, Anguilla anguilla, collected from a Mediterranean brackish environment and experimentally exposed to benzo[a]pyrene (B[a]P) and h-naphthoflavone (BNF). Eels were injected intraperitoneally at increasing doses (0.1, 1, 10, and 50 mg/kg wet body weight) using corn oil as a carrier and sacrificed after 7 days. The main objectives of the present study are: (1) to assess of the sensitivity of EROD induction as a biomarker to polycyclic aromatic hydrocarbon (PAH) exposure; (2) to determine an EROD dose–response relationship of the contaminants used; and (3) to compare the efficiency of B[a]P and BNF as inducers of EROD activity. Results showed that both chemicals resulted in a dose-dependent EROD induction, but increases were not linear. EROD activity seemed to reach a plateau at the exposure of 10 mg/kg in both treatment groups; B[a]P was a more potent inducer than BNF was at the higher doses (10 and 50 mg/kg), while the opposite result was observed at the lower ones (0.1 and 1 mg/kg). The greatest induction occurred in eels treated with 10 mg/kg B[a]P, in which a 261-fold increase in EROD activity was observed. Results showed that EROD activity in A. anguilla is significantly induced by B[a]P and BNF exposure, responding to a wide range of concentrations of these contaminants. We infer that this tool may be suited as a diagnostic biomarker for biomonitoring PAHs pollution in Mediterranean brackish environments and further field research is suggested